Sposoby rozwiązywania konfliktów organizacyjnych o podłożu międzykulturowym - Cisek, Sylwia; Fornalczyk, Agnieszka (Resolution strategies of cross-cultural organizational conflicts, 2006)
Research findings indicate that collaborative strategies are the most effective in producing a positive outcome from the conflict and in turn tend to reduce the negative one. The conflict issue is an important variable determining the use of collaborative or confrontational strategies. Correct-incorrect issues evoke the concern for group performance, which in turn encourage collaborative strategies. Right-wrong issues evoke the concern for social norms and gain-loss issues evoke the concern for personal interests. Both prompt confrontational strategies. Provided that most of organizational conflicts involve multiple issues it may be possible to induce collaborative strategies by focusing participants on proper issues.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1130, s. 337-345